La gestión administrativa en las instituciones educativas del circuito Aláquez-Joseguango Bajo, del distrito Latacunga. Diseño de un modelo de gestión estratégica. - Bungacho Gutiérrez, Alegría del Pilar (2016)
Strategic Management handbook it was made with the purpose of providing to the Educational Institutions Aláquez – Joseguango Bajo at Latacunga District, a tool to help in order to improve administrative management basing on four areas such as: resources, training, work area and academic level whose purpose is to achieve the institutional goals, the same that it is designed to have knowledge and understanding of management improvement and with this generates appropriate conditions for its development and continuous improvement. It did an analysis of the work areas that allow to assess something to improve educational management, contributing to the promotion of a process of continuous improvement of primary and secondary education, in order to know the importance of relevance that help to improve the education management by implementing strategies that allow an adequate development of teaching practice, guided at a better organization that helps to the comply with organizational goals.